2021
DOI: 10.3389/fphar.2021.706617
|View full text |Cite
|
Sign up to set email alerts
|

Astragalus Polysaccharide Reduces Blood Pressure, Renal Damage, and Dysfunction Through the TGF-β1-ILK Pathway

Abstract: Background:Astragalus polysaccharide extract (APS) has been shown to exhibit antioxidant and anti-inflammatory potential in the treatment of several diseases. However, whether APS could protect against renal damage in hypertensive mice is unknown.Methods: Hematoxylin and eosin staining, immunohistochemistry, real-time polymerase chain reaction, and Western blotting were used to investigate the effect of APS on the renal damage in deoxycorticosterone acetate- (DOCA) salt- and angiotensin II- (Ang II-) induced h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…It has been shown that single herbs (Liu et al, 2022;Qian et al, 2022), herbal extracts (Yu, 2020;Zheng et al, 2021;Cong et al, 2022;Ma et al, 2022), and Chinese medicine compounds (Chen et al, 2022a;Chen et al, 2022b;Wu et al, 2022;Zhao et al, 2022) have made great progress in the prevention and even treatment of renal fibrosis (Xu et al, 2021). They regulate multiple signaling pathways such as Wnt/β-catenin (Zhao et al, 2022), TGF-β1/Smad (Mao et al, 2019;Wu et al, 2022), Akt/mTOR (Lian et al, 2022), CX3CL1-RAF/MEK/ ERK (Hu et al, 2022b), mTORC1/p70S6K (Chen et al, 2019), SIRT1-NF-κB (Wang et al, 2018b), and interfere with different cytokine or inflammatory factors expression to regulate the development and progression of renal fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that single herbs (Liu et al, 2022;Qian et al, 2022), herbal extracts (Yu, 2020;Zheng et al, 2021;Cong et al, 2022;Ma et al, 2022), and Chinese medicine compounds (Chen et al, 2022a;Chen et al, 2022b;Wu et al, 2022;Zhao et al, 2022) have made great progress in the prevention and even treatment of renal fibrosis (Xu et al, 2021). They regulate multiple signaling pathways such as Wnt/β-catenin (Zhao et al, 2022), TGF-β1/Smad (Mao et al, 2019;Wu et al, 2022), Akt/mTOR (Lian et al, 2022), CX3CL1-RAF/MEK/ ERK (Hu et al, 2022b), mTORC1/p70S6K (Chen et al, 2019), SIRT1-NF-κB (Wang et al, 2018b), and interfere with different cytokine or inflammatory factors expression to regulate the development and progression of renal fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Frontiers in Pharmacology frontiersin.org Furthermore, APS inhibits the expression of MMP-2 and downregulates the expression of TIMP-1, TNF-α, and AngII (Lu and Wei, 2014;Sun et al, 2021). In addition, AS-IV inhibits multiple signaling pathways, including P38MAPK (Chen and Xie, 2019), TGF-β1/1-ILK (Zheng et al, 2021), and JAK/STAT (Guo et al, 2018). It also reduces the phosphorylation of P65 protein and effectively inhibits immune inflammation, apoptosis, and degradation of the extracellular matrix (ECM) in the renal tubular epithelium.…”
Section: Renal Tubular Epithelial Cellsmentioning
confidence: 99%
“…AS regulates numb/Notch/TGF-β1 pathway ( Yongping et al, 2015 ). APS inhibits TGF-β1/ILK pathway to reduce inflammation ( Zheng et al, 2021 ). ATS modulates PGC-1α and Bax/Bcl2/caspase3 pathway to inhibit apoptosis ( Li et al, 2022 ).…”
Section: Effect Of Astragalus On Fibrotic Diseasesmentioning
confidence: 99%
“…Nearly all kidney disorders have a common ultimate pathway, and growing renal fibrosis is linked to functional impairment ( Nastase et al, 2018 ). In hypertensive mice, TGF-β1/integrin-linked kinase (ILK) signaling pathway is activated, while it is downregulated after Astragalus polysaccharide treatment, as evidenced by reduced IL (interleukin)-1β, IL-6, α-SMA, collagen I, and collagen III ( Zheng et al, 2021 ). Renal tubulointerstitial fibrosis is made worse by EMT.…”
Section: Effect Of Astragalus On Fibrotic Diseasesmentioning
confidence: 99%
See 1 more Smart Citation